Adaptation of the methodology for sequential five-step fractionation of elements from bottom sediments of lake Imandra - Velieva Edae; Makarova Anna; Kharitonov Alexander (BIO Web of Conferences)
A series of experiments was carried out to adapt the technique of five-stage sequential fractionation of elements from soils, silts and bottom sediments (on the example of bottom sediments of Lake Imandra). The factors influencing the research by the method of five-stage sequential fractionation of elements from bottom sediments are considered. The results of changing the parameters of the extraction process are presented. The requirements for successful realization of experiments are formed. Application of adapted methodology for assessment of potential negative impact of pollutants in the system “bottom sediments - water” by fractionation of elements by physical and chemical mobility, potential bioavailability of elements in bottom sediments is proposed.